The Authority of Acting Regional Heads in Employee Mutation: Between Legality and Abuse of Power - Putri, Sofi Ekiana; Pratama, Agung Barok (Manabia: Journal of Constitutional Law, 2025)
This research examines the discretionary authority of Acting Regional Heads in implementing employee transfers regulated by the Ministry of Home Affairs Circular Letter No. 821/5492/SJ. The study focuses on the normative conflict between the Circular Letter and Government Regulation No. 49 of 2008, as well as its legal implications for governance. The research employs a normative juridical method with statutory and conceptual approaches. The findings indicate that the Circular Letter is inconsistent with the principle of legality and general principles of good governance, creating a potential for abuse of authority. The implications include disruption of good governance principles and an increased risk of bureaucratic politicization during transitional periods of regional leadership. This study highlights the need for regulatory harmonization and clear limits on discretionary powers of acting officials to ensure legal certainty and maintain the neutrality of civil servants. Keywords: Discretion, Acting Regional Head, Employee Transfer, Abuse of Power, Legality